1999
DOI: 10.4018/irmj.1999070101
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Correlates of Burnout in Information Systems Professionals

Abstract: The study examines the correlates of burnout in systems (IS) professionals. While there has been little previous research in the area of burnout among IS professionals, anecdotal evidence shows that burnout causes a negative impact on the peiformance of IS employees. These negative impacts can take the form of cynicism, dissatisfaction, and turnover (McGee, 1996). In this study we empirically examine the correlations of burnout with several work attributes that are considered to be either antecedents or conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 54 publications
(72 reference statements)
1
43
0
5
Order By: Relevance
“…For instance, Moore (2000) examined the lives of IT professionals and found that work overload was associated with work exhaustion, a significant predictor of turnover intentions. Sethi, Barrier, and King (1999) also found that work overload was associated with emotional exhaustion among IT workers. In addition, a recent study found that IT workers generally were much less likely to engage in organizational citizenship behaviors than their non-IT counterparts (Moore & Love, 2005).…”
Section: T a B L E I Antecedents To Work-life Conflictmentioning
confidence: 92%
“…For instance, Moore (2000) examined the lives of IT professionals and found that work overload was associated with work exhaustion, a significant predictor of turnover intentions. Sethi, Barrier, and King (1999) also found that work overload was associated with emotional exhaustion among IT workers. In addition, a recent study found that IT workers generally were much less likely to engage in organizational citizenship behaviors than their non-IT counterparts (Moore & Love, 2005).…”
Section: T a B L E I Antecedents To Work-life Conflictmentioning
confidence: 92%
“…Research has shown that emotional exhaustion (a core dimension of burnout) is linked to reduced job satisfaction (Burke & Greenglass, 1995;Maslach & Jackson, 1986;Pines, Aronson, & Kafry, 1981;Wolpin, Burke, & Greenglass, 1991); reduced organizational commitment (Jackson, Turner, & Brief, 1986;Leiter & Maslach, 1988;Sethi, Barrier, & King, 2004); and high turnover and turnover intention (Firth & Britton, 1989;Jackson et al, 1986). The research literature suggests that technology professionals are particularly vulnerable to work exhaustion (Kalimo & Toppinen, 1995;Moore, 2000a).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…IT professionals, specifically those in the software development fields are constantly plaque with the pressures to innovate and develop novel ideas. Job stressors such as work overload, role conflicts and role ambiguity are frequently associated with the IT profession (Li and Sham, 1991;Moore, 2000;Sethi et al, 1999), resulting in a reportedly high burnout levels among IT professionals compared to other occupations such as nurses and police (Huarng, 2001). Evidence in the literature also indicates that IT employees who experienced work stress and job burnouts tend to be dissatisfied with their jobs (Goodhue and Thompson, 1995;Li and Sham, 1991).…”
Section: Organizational Climate and Job Dissatisfactionmentioning
confidence: 99%